La fuerza vinculante de la OC-24/17 “Identidad de género, e igualdad y no discriminación a parejas del mismo sexo” para el Estado ecuatoriano (Tema Central) - León Moreta, María Augusta (2019)
Historically, LGTBI people have suffered stigmatization and structural violence from society and States. Through their constant struggle, LGTBI groups have achieved the recognition of several rights. However, the recognition of many others remains on a pending list. In Ecuador as well as in other countries in the region, the right to marry is still denied to same-sex couples. The Advisory Opinion OC- 24/17 “Gender identity, and equality and non-discrimination with regard to samesex couples”, handed down by the Inter-American Court of Human Rights, orders States parties of the Inter-American System to adopt all necessary measures to ensure access to marriage to same-sex couples. In Ecuador, the discussion focuses on the question of whether this advisory opinion would generate the obligation to register and celebrate marriages between same-sex couples, even without any legal reform. This article explores the reasons, why states have a duty to incorporate the standards established in this advisory opinion. Among these reasons are the obligation of the state authorities to conduct a control of conventionality as well as the principles of equality and nondiscrimination as consubstantial parts of the ius cogens. Another argument is that the Ecuadorian Constitution guarantees, through a series of principles, the direct and immediate application of more favourable rights and guarantees established in international instruments.